Gait Analysis Study of Runner Using Force Plate - Flaviana Catherine; Risti Suryantari (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Humans do regular physical activities such as running. Gait is forward  propulsion of the human body using lower extremities as a thrust. Humans gait pattern is characterized by their limbs movement in terms of velocity, ground reaction force, work, kinetic energy and potential energy cycle . Human gait analysis is used to assess, to plan, and to deliver the treatment for individuals based on the conditions that affect their ability to move. Gait analysis is commonly used in running sport to improve the efficiency of athletes in running and to identify problems related to their posture or movement. The aim of this research is to do running gait analysis study of human, using force plate which equipped by track board. The benefit of this study is to provide information, ideas and new perspectives about running and its prevention over an injury. The main method that will be discussed in this study is system design of gait analysis with specific setting, hardware and software, in order to acquire data(s).